Serum symmetric dimethylarginine concentrations in enalapril- or telmisartan-treated dogs with proteinuric chronic kidney disease - Nasr, Amirah; Lourenço, Bianca N.; Coleman, Amanda E.; Bartges, Joseph W. (Frontiers in Veterinary Science, 2024)
IntroductionRenin-angiotensin-aldosterone system inhibition (RAASi) reduces intraglomerular pressure and is a standard therapy for dogs with proteinuric chronic kidney disease (CKD). RAASi can acutely decrease glomerular filtration rate (GFR); however, its effects on the marker of GFR serum symmetric dimethylarginine (SDMA) concentration in dogs have not been specifically evaluated. The objective of this study was to evaluate changes, relative to pretreatment values, in serum SDMA concentrations in dogs with proteinuric CKD receiving RAASi therapy.MethodsThis retrospective study used banked samples from 29 dogs with proteinuric CKD treated with enalapril (0.5 mg/kg PO q12h; n = 16) or telmisartan (1 mg/kg PO q24h; n = 13) alone (n = 22) or in combination with amlodipine if severely hypertensive (n = 7). Serum SDMA, creatinine, and urea nitrogen (SUN) concentrations were measured before and 7 and 30 days after starting RAASi. Percentage and absolute changes in these biomarkers were calculated for each dog and time point. A linear mixed model was used to test whether changes significantly differed from zero (α < 0.05).ResultsOverall, mean ± SEM Day 7 and 30 percentage change in SDMA were  − 4.8 ± 3.6% and  − 3.2 ± 3.4%, respectively; in creatinine were 7.4 ± 3.3% and 3.0 ± 3.1%, respectively; and in SUN were 22.1 ± 6.8% and 16.7 ± 6.2%, respectively. Mean changes varied according to whether all dogs, those on RAASi alone, or those co-treated with amlodipine were evaluated. In dogs receiving RAASi alone, at day 7, there were significant mean percentual increases in creatinine (9%; p = 0.023) and SUN (23%; p = 0.005), but SDMA was unchanged. In dogs co-treated with amlodipine, a significant absolute decrease in mean SDMA (−2.29 μg/dL; p = 0.026) occurred at days 7 and 30, while mean creatinine was unchanged and mean SUN increased.DiscussionProteinuric dogs receiving RAASi had low-magnitude changes in serum SDMA and creatinine, and moderate-magnitude changes in SUN concentrations. The direction of change in SDMA did not consistently match that of creatinine and SUN.